2021
DOI: 10.3390/microorganisms9020234
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Endophytic, Rhizospheric and Epiphytic Colonization of Vitis vinifera by the Plant-Growth Promoting and Antifungal Strain Pseudomonas protegens MP12

Abstract: An evaluation was conducted of the colonization of Pseudomonas protegens MP12, a plant-growth promoting and antagonistic strain, inoculated in vine plants during a standard process of grapevine nursery propagation. Three in vivo inoculation protocols (endophytic, rhizospheric, and epiphytic) were implemented and monitored by means of both culture-dependent and independent techniques. Endophytic treatment resulted in the colonization of the bacterium inside the vine cuttings, which spread to young leaves during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Identifying microbial species is very relevant because the beneficial activity is characteristic of certain species [ 14 ]. Bacterial species found in this work belonging to the genera Enterobacter , Pantoea , Pseudomonas , and Serratia have been successfully studied as PGPM in several crops [ 4 , 5 , 8 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In the case of Pseudomonas allii , it has also been reported as a plant pathogen responsible for soft rot in onions [ 50 ]; even though the plants in this study did not show disease symptoms, further experiments must be performed at later stages of plant development to determine their safety.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying microbial species is very relevant because the beneficial activity is characteristic of certain species [ 14 ]. Bacterial species found in this work belonging to the genera Enterobacter , Pantoea , Pseudomonas , and Serratia have been successfully studied as PGPM in several crops [ 4 , 5 , 8 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In the case of Pseudomonas allii , it has also been reported as a plant pathogen responsible for soft rot in onions [ 50 ]; even though the plants in this study did not show disease symptoms, further experiments must be performed at later stages of plant development to determine their safety.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the biological control of Rhizoctonia solani on Mentha piperita showed that Pseudomonas fluorescens had the highest in vitro inhibition of the pathogen and was effective in reducing the disease under greenhouse conditions (23%), although T. viride and B. subtilis also reduced the incidence to 50% [ 21 ]. The main concern with the use of soil-applied biological control agents is the colonization and persistence of the microbial inoculum in plants due to abiotic factors such as temperature, humidity, soil conditions or biotic factors such as antagonism, competition, predation, among others that may reduce their efficacy under field conditions [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…During a standard process of grapevine nursery propagation, epiphytic and rhizospheric inoculation by the PGPR strain Pseudomonas protegens MP12 was effective in controlling an artificially induced Botrytis cinerea infection in detached leaves. The success of rhizospheric and leaf colonization in vine plants suggests a potential for the future exploitation of P. protegens MP12 as a biofertilizer and biopesticide [221].…”
Section: Trichoderma Sppmentioning
confidence: 99%